A "Quıet" need ın the dısaster of the century: a qualıtatıve study on menstrual hygıene management - Ayşe Aydın; Meltem Şirin Gok; Bahar Çiftçi (BMC Public Health)
Abstract Introduction On February 6, 2023, a devastating earthquake centered in Kahramanmaraş, Turkey, affected millions of people, forcing many to live in tent cities. Although menstrual hygiene is a basic need, it is often overlooked in disaster settings. This study aims to explore the problems and experiences related to menstrual hygiene management among women living in tent cities following the earthquake. Methods This qualitative study was conducted in June 2023 with 12 women living in tent cities caused by the earthquake. Data were collected through semi-structured interviews conducted via Zoom. Each interview lasted approximately 30 min. The interviews were analyzed using content analysis, and themes and sub-themes reflecting the women's experiences were identified. Results The content analysis revealed two main themes: "Challenges Related to Menstrual Hygiene" and "Additional Issues Related to the Menstrual Period." The first theme included difficulties accessing materials, problems with disposing of hygiene products, inadequate physical environments, and challenges related to religious rituals. The second theme highlighted changes in menstrual cycles, lack of access to comforting practices, and neglect of personal needs. The findings showed that menstrual hygiene management is an urgent yet often overlooked need during disaster periods. Conclusion This study demonstrates that menstrual hygiene management is critical in disaster response efforts. Effective menstrual hygiene management is essential for protecting women's privacy and dignity. Healthcare professionals play a vital role in identifying these needs, ensuring the supply of hygiene materials, providing appropriate environments, and offering education to women. Integrating menstrual hygiene management into disaster response plans is crucial for improving women's health and well-being.